2020
DOI: 10.3390/nu12020369
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Menopausal Effects of Cornus officinalis and Ribes fasciculatum Extract In Vitro and In Vivo

Abstract: Natural herbal medicines have been developed for the treatment and prevention of women’s menopausal symptoms. In this study, we investigated the anti-menopausal effects of Cornus officinalis (CO) and Ribes fasciculatum (RF) extracts in 3T3-L1 preadipocytes, MC3T3-E1 preosteoblasts, and COV434 granulosa cells in vitro and ovariectomized (OVX) ddY mice in vivo. Combination treatment of CO and RF extract at 7:3 ratio inhibited lipid accumulation via Plin1 and Adipoq downregulation in a cocktail of dexamethasone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…These adipogenic-related genes stimulate adipocyte differentiation of 3T3-L1 cells and differentiated adipocytes were apparently by lipid-rich accumulation, which is histologically stained by oil red O [47]. In previous studies, a CO-containing formulation inhibited the expression of Pparg and Cebpa [48] and a mixture of CO and RF extracts reduced ovariectomized (OVX)-induced weight gain in mice [49]. Our results show that CO and RF extracts significantly suppressed the expression of Pparg and Cebpa, which may, in turn, decrease the expression of Fabp4, because Fabp4 is a target gene of Pparg and Cebpa.…”
Section: Discussionmentioning
confidence: 96%
“…These adipogenic-related genes stimulate adipocyte differentiation of 3T3-L1 cells and differentiated adipocytes were apparently by lipid-rich accumulation, which is histologically stained by oil red O [47]. In previous studies, a CO-containing formulation inhibited the expression of Pparg and Cebpa [48] and a mixture of CO and RF extracts reduced ovariectomized (OVX)-induced weight gain in mice [49]. Our results show that CO and RF extracts significantly suppressed the expression of Pparg and Cebpa, which may, in turn, decrease the expression of Fabp4, because Fabp4 is a target gene of Pparg and Cebpa.…”
Section: Discussionmentioning
confidence: 96%
“…Combined treatment of CO and RF has become well-known traditional herbal agents during the past decade. Previous studies showed that combined CO and RF extracts had synergistic effects on anti-menopausal syndrome and anti-obesity [ 26 , 27 ]. CO and RF mixture decreased adipocyte differentiation in 3T3-L1 pre-adipocytes, through the downregulation of adipogenic markers such as Adipoq , Fabp4 , Pparg , Srebp1 , and Plin1 [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that combined CO and RF extracts had synergistic effects on anti-menopausal syndrome and anti-obesity [ 26 , 27 ]. CO and RF mixture decreased adipocyte differentiation in 3T3-L1 pre-adipocytes, through the downregulation of adipogenic markers such as Adipoq , Fabp4 , Pparg , Srebp1 , and Plin1 [ 26 , 27 ]. Differentiation of adipocyte is characterized by lipid accumulation [ 33 ], CO and RF mixture also inhibited the number of lipid droplets in the cytoplasm of 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations